DEVELOPMENT OF INTEGRATED SCIENCE E-MODULES ETHNOSAINS-BASED ON SUBSTANCE, TEMPERATURE AND HEAT FOR VII GRADE - Fitri, Yosi Elza; Zahra, Firda Az (Universe, 2024)
During the COVID-19 pandemic, learning is carried out online, to answer the challenges of online learning, it is necessary to make teaching materials that can be used from home, such as electronic modules. This study aims to produce an E-Module in Ethnosains-Based Integrated Science on Materials of Substance, Temperature, and Heat for VII Grade Students that is valid and practical. This type of research is Research and Development (R&D) using a 4D model, but the research only goes up to three stages including the define, design and develop stages. Based on the results of the study through the validity test of the E-Module, it obtained a validation scored of 85,82% with a valid category. The practical test by the teacher scored 90,74% in the very practical category and the practical test by the students scored 95,15% in the very practical category.